THE RELIGIOUS VIEWS OF TULSI DAS - Babineau, Edmour (My University, 1972)
A study of religious views of Tulsi Das, as expressed in the Ramearitmanas, compares with those Valmiki, as expressed in the Ramayana.
Keywords: Religion; Religion